PENGENDALIAN KOMPUTER JARAK JAUH DENGAN MEMANFAATKAN JARINGAN INTERNET BERBASIS PERANGKAT LUNAK - Agus Sugiharto (Fakultas Ilmu Komputer dan Desain - Unsurya, 2015)
The phenomenon of a big city in Indonesia such as Jakarta in particular, with a wide range of business sense is always tied and pursued by a tight time schedule and make everything should be in good management, on the one hand there is a computer application program disorder / damage and should be fixed at that moment while the place (office, home) no one will understand it as the venue hire a consultant for computer maintenance. The condition of the road with busy traffic congestion and have to throw at least the time should be used appropriately.Remote computer control is one solution, with this remote computer control between technicians and the user does not need to be met, by simply calling a computer consultant / technician then connect the computer to the intenet, then in a matter of hours or minutes, the user's application program has been